Working in the Same Sector, in the Same Organization and in the Same Occupation: Similarities and Differences Between Women and Men Physicians’ Work Climate and Health Complaints - Falkenberg, Helena; Näswall, Katharina; Lindfors, Petra; Sverke, Magnus (Nordic Journal of Working Life Studies, 2015)
Due to the segregated labor market, gender differences in health are often confounded by factors such as sector or occupation. This study explored similarities and differences in work climate and health complaints among women and men working in the same sector, in the same organization, and in the same occupation. First, work climate and health complaints were compared between women and men. Second, relations between the work climate and health complaints were investigated in both genders. Questionnaire data were collected from 95 women and 105 men physicians who worked in the same acute care hospital in Sweden. The results showed no gender differences in the job, role, leadership, or organizational characteristics. However, women physicians reported less workgroup cohesiveness and cooperation and more mental and physical health complaints than men physicians. Workgroup cohesiveness and cooperation were related to less health complaints only for men physicians. This explorative study indicates similarities between women and men when the work situation is similar, but suggests that some of the differences that appear in the large structures of the gender-segregated labor market also seem to be present for women and men who work in the same sector, in the same organization, and in the same occupation.